Denosumab Reduces Cortical Porosity of the Proximal Femoral Shaft in Postmenopausal Women With Osteoporosis. (19th May 2016) - Zebaze, Roger; Libanati, Cesar; McClung, Michael R; Zanchetta, José R; Kendler, David L; Høiseth, Arne; Wang, Andrea; Ghasem‐Zadeh, Ali; Seeman, Ego
ABSTRACT: Hip fractures account for over one‐half the morbidity, mortality, and cost associated with osteoporosis. Fragility of the proximal femur is the result of rapid and unbalanced bone remodeling events that excavate more bone than they deposit, producing a porous, thinned, and fragile cortex. We hypothesized that the slowing of remodeling during treatment with denosumab allows refilling of the many cavities excavated before treatment now opposed by excavation of fewer new resorption cavities. The resulting net effect is a reduction in cortical porosity and an increase in proximal femur strength. Images were acquired at baseline and 36 months using multidetector CT in 28 women receiving denosumab and 22 women receiving placebo in a substudy of FREEDOM, a randomized, double‐blind, placebo‐controlled trial involving women with postmenopausal osteoporosis. Porosity was quantified using StrAx1.0 software. Strength was estimated using finite element analysis. At baseline, the higher the serum resorption marker, CTx, the greater the porosity of the total cortex ( r  = 0.34, p  = 0.02), and the higher the porosity, the lower the hip strength ( r  = –0.31, p  = 0.03). By 36 months, denosumab treatment reduced porosity of the total cortex by 3.6% relative to baseline. Reductions in porosity relative to placebo at 36 months were 5.3% in total cortex, 7.9% in compact‐appearing cortex, 5.6% in outer transitional zone, and 1.8% in inner transitional zone (all p  < 0.01). The improvement in estimated hip integral strength of 7.9% from baseline ( p  < 0.0001) was associated with the reduction in total porosity ( r  = –0.41, p  = 0.03). In summary, denosumab reduced cortical porosity of the proximal femoral shaft, resulting in increased mineralized matrix volume and improved strength, changes that may contribute to the reduction in hip and nonvertebral fractures reported with denosumab therapy. © 2016 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research (ASBMR).